PENGARUH PERILAKU PEMIMPIN, KARAKTERISTIK PRIBADI PEGAWAI, DAN SIFAT PEKERJAAN TERHADAP MOTIVASI PEGAWAI DI DINAS PENDIDIKAN PROVINSI DKI JAKARTA - Arita Marini (Jurnal Manajemen Pendidikan, 2010)
The staff’s motivation is assumed to be significantly affected by their leader’s behavior, their personal characteristics, and the nature of their tasks. The causal study reported here aimed to examine the hypothesis. It was conducted in the Educational Office of the DKI Jakarta Province, through a four-month survey, from May 2009 to September 2009, involving 150 staff members who had been randomly selected from the overall 247 staff members. The data of each variable were collected separately by the respondents’ filling in a questionnaire. A path technique was employed to analyze the data. The results show positively direct effects of the leader’s behavior, the staff’s personal characteristics, and the nature of their tasks on their work motivation. A positively direct effect of the leader’s behavior was also apparent on the staff’s personal characteristics and also the nature of their tasks. But the leaders’ behavior showed a positively indirect effect on the staff’s motivation through their personal characteristics and the characteristics of their tasks. The findings suggest that variation in the staff’s motivation could be minimized if the variables of the leader’s behavior, the staff’s personal characteristics, and the nature of their tasks are taken into consideration.